Efektifitas Penggunaan Media Flash Card Terhadap Peningkatan Mufradat Siswa Kelas VII Mts Al- Intishor, Mataram - Asirri, Shelina; Suparmanto, Suparmanto; Handayani, Yusi (Al Ibrah: Journal of Arabic Language Education, 2023)
This research utilized a qualitative research method to evaluate the effectiveness of using flashcards in enhancing Arabic vocabulary among seventh-grade students at Mts Al Intishor Mataram. Data were collected through observations, interviews, and documentation. The observations revealed that flashcards can generate enjoyment and interest among students in vocabulary learning. However, the test results indicated variations in students' abilities to answer vocabulary-related questions after using flashcards. The research findings demonstrated that the use of flashcards can enhance students' ability to memorize vocabulary, although some students encountered difficulties in recalling and comprehending vocabulary developed into questions. Based on the research findings, it can be concluded that the utilization of flashcards in Arabic vocabulary learning is effective in improving students' proficiency. However, it is recommended to use this media approach in 3 to 4 sessions for more effective outcomes.Top of FormBottom of Form